The impact of having a free community eye clinic located inside a homeless shelter: a retrospective analysis of patient demographics - Ahluwalia, Amit; Morcos, David; Koulen, Peter (Frontiers in Public Health, 2023)
Worsening vision is a life-altering process that affects individuals in many aspects of daily life. While worsening vision can be caused by normal physiological processes that occur with age, there can be underlying systemic or ocular diseases that may be the root cause. Routine eye exams can screen for disease as well determine the degree of vision correction required to attain acceptable vision. Access to an eye exam ordinarily requires vision insurance and one must consider the added expense of glasses if they are recommended. While this can be a life-improving visit for many, there are several socioeconomic barriers that discourage homeless and low-income individuals from being able to access this service. The lack of resources to access regular eye exams and the resulting inadequate eye care may lead to underdiagnosis of serious ocular pathology. The Kansas City Free Eye Clinic is located inside a homeless shelter and, therefore, provides a convenient location for homeless and low-income individuals to receive comprehensive eye exams as well as prescription glasses at no cost. In this paper, we discuss the unique setup and demographics of this student-run eye clinic and the ways in which it has served the Kansas City population and how its integration into a homeless shelter could serve as a role model for free community eye clinics.